Smart machinery monitoring system berbasis mobile application - Maulana, Gun Gun; Aminah, Siti; Rahman, Fikri Abdul (Universitas Nusantara PGRI Kediri, 2024)
This research designs and implements a Mobile Application-Based Smart Machinery Monitoring System as a solution for monitoring machine conditions in industrial environments. Using Flutter as a mobile application development framework and utilizing internet connection capabilities, this research aims to increase monitoring efficiency and minimize the risk of machine failure. With a responsive interface, this application allows real-time access to machine conditions from various mobile devices. Internet of Things (IoT) integration allows machine sensors to communicate with applications, providing accurate and direct data. This research is expected to make a positive contribution to industrial operational efficiency, make it easier for users to monitor machine conditions, and support the industry's evolution towards an era of better connectivity.